PENGEMBANGAN MEDIA PANCASILA ULAR TANGGA (PANCA LAGA) UNTUK MENINGKATKAN CIVIC KNOWLEDGE PADA PESERTA DIDIK KELAS II MI NEGERI 5 MAGELANG - Anisatun Nafiah, Siti (UHN IGB Sugriwa Denpasar, 2025)
This study aims to (1) develop the Pancasila Snakes and Ladders learning media (Panca Laga) to enhance civic knowledge in the Pancasila Education subject for Grade II students at MI Negeri 5 Magelang, and (2) analyze the feasibility of the Pancasila Snakes and Ladders media (Panca Laga) in improving civic knowledge among those students. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). However, this study was limited to the development stage due to the research focus on product generation and constraints related to time, resources, and cost. Data collection techniques included observation, interviews, questionnaires, documentation, and both quantitative and qualitative data analysis. Quantitative data were obtained from media and material experts, while qualitative data were collected from interviews with Grade II homeroom teachers. The results of the needs analysis indicated that students responded positively to the development of the Pancasila Snakes and Ladders media (Panca Laga). The required criteria included: attractive and content-supporting illustrations; simple, communicative, and interactive language; and full-color printed media. Based on expert validation questionnaires, the media received an overall score of